COLOUR AND ANTIOXIDANT PROPERTIES OF COCOA BEANS FROM PODS STORAGE AND FERMENTATION USING SHALLOW BOX - Sulaiman, Khairul Bariah; Yang, Tajul Aris; Ariffin, Fazilah (MATTER: International Journal of Science and Technology, 2017)
The study aims to evaluate the effect of duration during pods storage and fermentation using a shallow box technique on the colour and antioxidant properties of the cocoa beans. The fermentation experiment was conducted at the Cocoa Research and Development Centre Bagan Datuk, using 150 kg of fresh cocoa seeds from four pods storage duration (0, 2, 4 and 6 days). A total of 15 kg of samples were taken out randomly for the duration of 0, 24, 48, 72, 96 and 120 hours of fermentation and subjected to sun drying. The dried samples were analyzed by the score of equivalent percent fully brown (EB), Browning index (BI) and antioxidant properties by Ferric Reducing Power (FRAP) Test. The results demonstrated that EB scores increased significantly (P <0.05) from 37%, 34%, 47% and 42% at 0 hours for PS0, PS2, PS4 and PS6, respectively to 87%, 93%, 95% and 94% after 120 hours of fermentation. Similarly, significant (P<0.05) increased of the BI to more than 1.00 after 48 hours for PS4 and PS6, whereas at 72 hours of fermentation for PS0 and PS2, respectively. On the other hand, the antioxidant properties fluctuated with respect to the different duration of fermentation.